‏ The Impact of Training and Health Education on Improving Health Security - Nasser, Alburayk, Alhanouf; Ahmed, Alghamdi, Haneen; Abdullah, Alashwan, Ali; Abdullah, Alothman, Mohammed; Abdullah, Alsufyani, Rahaf; Fahad, Binthunayyan, Samar; Sami, Albinahmed, Hisham; A. Al Rushud, Muath; Zakri, Ahmed Yahya; Alshalawi, Alhanouf Saad (Journal of Ecohumanism, 2024)
Background: Health security is critical for protecting populations from health threats such as infectious diseases and public health emergencies. Training and health education are proactive strategies that enhance individual and community resilience, strengthen health systems, and improve preparedness for crises. This study examines the impact of structured training and health education interventions on improving health security outcomes. Methods: A quasi-experimental design with pre-test/post-test assessments was employed. The study involved 100 participants recruited through convenience sampling from a community health center setting. The intervention consisted of an eight-session program delivered over four weeks, covering topics such as hygiene, infection control, emergency preparedness, and vaccination awareness. Data were collected using validated questionnaires and focus group discussions, with quantitative analysis performed using SPSS and qualitative data analyzed thematically. Results: Post-intervention results showed significant improvements in knowledge, attitudes, and practices related to health security. High knowledge levels increased from 18.3% to 74.2%, positive attitudes rose from 26.7% to 80%, and good practices improved from 18.3% to 66.7%. Paired sample t-tests confirmed statistically significant gains across all domains (p < 0.001). Qualitative feedback highlighted enhanced engagement and confidence among participants.Conclusion: The study demonstrates that targeted training and health education interventions effectively improve health security by enhancing knowledge, attitudes, and practices. These findings underscore the importance of integrating such programs into health systems to build resilient communities capable of addressing public health emergencies.